Sugiyama, Kimi (audio interview #2 of 2) - Sugiyama, Kimi (1901 - 1996); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - Kimi Sugiyama was interviewed in the home of her son and daughter-in-law with whom she lived at the time of the interview. The home was located near Virginia Country Club. TOPICS - Japanese farmers; Bixby Ranch; Santa Anita Racetrack; and internment;internment; Jerome, Arkansas; military; children; education; and the Pike;oil wells; Japanese farmers; and internment; 5/28/1980